2000
DOI: 10.1038/sj.ejcn.1600959
|View full text |Cite
|
Sign up to set email alerts
|

High fruit intake may reduce mortality among middle-aged and elderly men. The Study of Men Born in 1913

Abstract: Objective: A number of long-term population-based studies have tried to study fruit and vegetable consumption in relation to cardiovascular disease, cancer and total mortality. Few of these studies are based on randomly selected population samples. The aim of the study was to investigate the long-term effect of fruit and vegetable consumption on mortality, cardiovascular disease, cardiovascular death, cancer morbidity and cancer death among middle-aged and elderly men. Design: Prospective cohort study. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 17 publications
(17 reference statements)
7
49
0
Order By: Relevance
“…The most socially deprived regions of Scotland have the highest mortality from coronary heart disease in Britain, and evidence from the Scottish Heart Health Study 29,30 suggested that lack of fruit and vegetables in the diet may possibly play a role in addition to the classical risk factors for cardiovascular disease. In agreement with this was a study of elderly Swedish men who had been followed for 26 years 31 , since daily fruit consumption seemed to have a positive effect on longterm survival independently of traditional risk factors such as smoking, high blood pressure and plasma cholesterol.…”
Section: Discussionsupporting
confidence: 66%
“…The most socially deprived regions of Scotland have the highest mortality from coronary heart disease in Britain, and evidence from the Scottish Heart Health Study 29,30 suggested that lack of fruit and vegetables in the diet may possibly play a role in addition to the classical risk factors for cardiovascular disease. In agreement with this was a study of elderly Swedish men who had been followed for 26 years 31 , since daily fruit consumption seemed to have a positive effect on longterm survival independently of traditional risk factors such as smoking, high blood pressure and plasma cholesterol.…”
Section: Discussionsupporting
confidence: 66%
“…These studies, however, are inconclusive because they often lack appropriate adjustments for confounding (eg, confounding by age because obese persons are generally 7 years younger at time of their first MI than normal-weight individuals), but they stress the need for high-quality additional research. Finally, population-based cohort studies that study all-causes mortality in relation to the intake of fruits and vegetables, [87][88][89][90] whole grains, 87,91,92 legumes, 93 nuts, 94,95 or salt 96 -98 are scarce but are generally supportive of a protective effect of the recommendations.…”
Section: Regular Fish (Oil) Consumptionmentioning
confidence: 99%
“…However, studies of a London cohort showed that cardiovascular risk factors in adulthood are more strongly related to adult than to childhood socio-economic circumstances 5 . Alongside this, epidemiological evidence suggests that certain foods, in particular fruit and vegetables, protect against CVD 6,7 and some cancers 8 , and that a high intake of dietary fat is associated with increased risk for CVD, obesity and type II diabetes 9 .…”
mentioning
confidence: 99%